Democracy and the environment: a bibliometric study of scientific production (Research, Society and Development, 2020)
The negative environmental impacts resulting from different human activities, especially those of an economic nature, have led different spheres such as the State, private initiative and civil society to jointly seek solutions to environmental problems and reduce their impact on the social fabric, as well as the understanding that such solutions may be related to democracy. Thus, these factors have aroused the interest of the academy in contributing to the maturing of the discussion on the relationship between democracy and the environment. This study aims to conduct a bibliometric study of scientific production that deals with the relationship between the environment and democracy, which has been produced in the literature by the terms: green democracy, ecological, sustainable and environmental democracy. For this purpose, the methodological path adopted was the bibliometric procedure in the mapping of the productions published, between 1944 and 2019, in the international databases Scopus and Web of Science, and counted on the support of the software VOSviewer® version 1.6.11 and the interpretative analysis, to make the analysis of the 118 articles considered. The nine clusters identified include 18 authors with at least 29 citations, each cluster presents a small number of papers and authors and does not maintain links between them, which results in a relatively high dispersion of publications, however, one point in common can be noted: participation, even if approached in different ways.